Model Matematika dan Simulasi Penyebaran Perokok Dalam Suatu Populasi Menggunakan Matlab - Roni Al Maududi; Rini Widia Putri Z; Purni Munah Hartuti (UIN Imam Bonjol Padang, 2023)
One of the social problems that is still controversial is smoking. This is closely related to public health, because smokers have a great risk of spreading disease either directly to smokers themselves or indirectly to other people who do not smoke but are in the same environment or population as smokers, such as cancer, heart disease. , caries, and others caused by the substance content of the smoked cigarettes. The more smokers in a population, the greater the chance of increasing the number of smokers in that population, which directly or indirectly means increasing the spread of the diseases that have been mentioned. The purpose of this research is to construct a mathematical model and simulate the distribution of smokers in a certain population using Matlab. The variables that make up the Mathematical model are divided into 3 classes, namely prospective smokers (), regular smokers (), and ex-smokers (). The method used in this research is the method of literature study and literature related to research and simulation using Matlab. At the end of the study, the value of the basic reproduction number () will be analyzed to determine the dynamics that occur in the population and the simulation results of the mathematical model formed. The results of this study are a depiction of how much influence the presence of smokers has in a population by looking at the parameters that affect changes in the value significantly.